Combustion properties of gaseous CH4/O2 coaxial jet flames in a single-element combustor. (15th November 2016) - Kim, Tae Young; Choi, Sun; Kim, Hee Kyung; Jeung, In-Seuck; Koo, Jaye; Kwon, Oh Chae
Highlights: Stability of GCH4 /GO2 coaxial jet flames is greatest at fuel-rich condition. Ignition limits are restricted compared with steady combustion stability limits. Stable, attached flames and oscillating, near-blowout flames are observed. Laminar-to-turbulent transition-like flame behavior is found due to use of pure O2 . A database for modeling combustion of CH4 /O2 bipropellants in combustor is given. Abstract: Fundamental combustion properties of gaseous methane (CH4 )/oxygen (O2 ) coaxial jet flames in a single-element combustor are experimentally evaluated as a preliminary step for subsequent studies of injection at very low temperature or using liquid O2 for CH4 /O2 bipropellants, recently appearing to be the oncoming liquid bipropellant. A combustion chamber with quartz windows, a single shear coaxial injector and an exhaust nozzle on the downstream of the chamber is considered for the present study. Focusing on the measurements of the ignition and combustion stability limits of the coaxial jet flames in the chamber, flame visualization is also conducted by OH ∗ chemiluminescence, schlieren imaging and direct imaging. Results show the ignition limits restricted than the combustion stability limits. Flame behaviors are largely classified into two, the stably attached flame and the oscillating, liftoff (near-blowout) flame. Due to cooling effects on the wall of the chamber, stably liftoff flame is not observed. The stability of the flame is greatest at fuel-rich condition (based on the injected amounts of CH4 and O2 ). From the flame visualization flame thickness is found to be smaller than the injector lip thickness and insensitive to injection conditions. The laminar-flow behavior near the injector exit due to the strong burning of pure O2 is observed even for high Reynolds numbers ( Re ). The flame visualization also exhibits the recirculating O2 that enhances burning in the combustor through the reaction with the outer fuel jet. The results of ignition limits, combustion stability limits and flame visualization can be used as a database for researches of modeling the gaseous CH4 /O2 jet flames in the combustion chamber.